ANALYSIS OF THE DIFFERENCES IN THE PUBLIC PROSECUTOR’S CHARGES AGAINST NARCOTICS DEALERS (A STUDY OF DECISION NUMBER 1178/PID.SUS/2025/PN MDN AND DECISION NUMBER 1478/PID.SUS/2025/PN MDN) - Teguh Tri Setiawan; Tri Reni Novita (CV. Barokah Publsiher, 2026)
Narcotics sellers in Decision Number 1178 / Pid.Sus / 2025 / PN Mdn and Decision Number 1478 / Pid.Sus / 2025 / PN Mdn consists of different weight of evidence, different location and time of arrest of the defendant, the demands are also different, namely 9 years with 7 years. The factors causing the disparity in prosecutors' demands in narcotics sales cases in Decision Number 1178 / Pid.Sus / 2025 / PN Mdn and Decision Number 1478 / Pid.Sus / 2025 / PN Mdn are the factors of legislation that do not limit with certainty, factors of aggravating and mitigating factors. The impact of the disparity in the prosecutor's demands on law enforcement and justice for the defendant in Decision Number 1178 and Decision Number 1478 is that it can reduce the sense of justice and public trust in the criminal justice system, as well as hinder efforts to eradicate narcotics effectively and fairly.